Disruption of Proteostasis by Natural Products and Synthetic Compounds That Induce Pervasive Unfolding of Proteins: Therapeutic Implications - Nuria Vilaboa; Juan Antonio Lopez; Marco de Mesa; Clara Escudero-Duch; Natalie Winfield; Melanie Bayford; Richard Voellmy (MDPI AG, 2023)
Exposure of many cancer cells, including multiple myeloma cells, to cytotoxic concentrations of natural products celastrol and withaferin A or synthetic compounds of the IHSF series resulted in denaturation of a luciferase reporter protein. Proteomic analysis of detergent-insoluble extract fractions from HeLa-derived cells revealed that withaferin A, IHSF058 and IHSF115 caused denaturation of 915, 722 and 991 of 5132 detected cellular proteins, respectively, of which 440 were targeted by all three compounds. Western blots showed that important fractions of these proteins, in some cases approaching half of total protein amounts, unfolded. Relatively indiscriminate covalent modification of target proteins was observed; 1178 different proteins were modified by IHSF058. Further illustrating the depth of the induced proteostasis crisis, only 13% of these proteins detectably aggregated, and 79% of the proteins that aggregated were not targets of covalent modification. Numerous proteostasis network components were modified and/or found in aggregates. Proteostasis disruption caused by the study compounds may be more profound than that mediated by proteasome inhibitors. The compounds act by a different mechanism that may be less susceptible to resistance development. Multiple myeloma cells were particularly sensitive to the compounds. Development of an additional proteostasis-disrupting therapy of multiple myeloma is suggested.